“Non c’è più un tempo fuori”. Accelerazione del tempo e compressione dello spazio nell’esperienza del lavorare da casa durante la pandemia - Burchi, Sandra (SocietàMutamentoPolitica, 2023)
The article proposes a reading of the changes that occurred with regard to the use of time, during the experience of confinement, and focuses in particular on the impact of the experience of working from home. The results of a research conducted the period of the pandemic furnish the backdrop of this analysis. The hypothesis is that the practice of working from home, looked at from the perspective of time patterns, has a normalizing effect in terms of the plurality and multiformity of patterns that govern daily life. The time of the everyday – viewed by the sociology of time as a resistant time with respect to the mechanisms that regulate social life – is forced to absorb and catalyse the characteristics of an all-productive time, and to come to terms with the phenomena of acceleration that regulate social life. The Foucauldian category of “ disciplining “ has been used to describe the effects brought about by the use of domestic space upon the perception and quality of temporal patterns.